Persepsi Mahasiswa Akuntansi Mengenai Faktor-Faktor yang Mempengaruhi Pemilihan Karier sebagai Akuntan Publik - M Riza Ramadhan (Journal on Education, 2024)
This research examines the factors that influence students' career choices to become public accountants. This research was conducted at the Faculty of Economics and Business, University of Lampung, with 100 respondents. This research was conducted using a questionnaire method via Google Form. The results of this research show that finances, professional training, professional recognition, social values, and work environment have an influence on accounting students' career choices in becoming public accountants.